THE EFFECT OF SERVICE QUALITY AND UTILIZATION OF INFORMATION TECHNOLOGY ON CONSUMER LOYALTY DURING THE COVID-19 PANDEMIC - Siti Nurjanah; Melitina Tecoalu; Eka Desy Purnama (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
In this era of globalization, sharp business competition followed by the progress of the global economy encourages all sectors of business growth. Every business actor is required to be sensitive to any changes that occur and place an orientation to customer satisfaction as the main goal. The consequence of modernization and technology today is that companies must be able to work extra hard to present the best products with the best service to consumers with technological innovations. Coupled with the COVID-19 condition that hit Indonesia, causing PT. Maybank Indonesia Finance, which experienced a decline in sales and financing, needed to reorganize its corporate strategy. This quantitative research took a study at PT. Maybank Indonesia Finance, with 100 respondents who are debtors throughout Indonesia using SMARTPLS 3.3 data processing. The results showed that Service Quality had an influence on Consumer Loyalty mediated by Consumer Satisfaction, but the use of Information Technology in the form of the Maybank Mobile Application did not affect Consumer Loyalty mediated by Consumer Satisfaction.